Fuzzy finite element solution of uncertain convection-diffusion heat transfer for a rectangular plate - Sudipta Priyadarshini; Sukanta Nayak (Computational Algorithms and Numerical Dimensions)
In the recent development of fluid flow and industrial problems, convection-diffusion of heat transfer plays an important role. One can see the same is greatly affected by epistemic types of uncertainties due to involved parameters, boundary conditions, and material properties. Therefore, we focus on numerical approaches to handling uncertainties. In addition, the Finite Element Method (FEM) is adopted with the fuzzy environment to investigate the uncertain temperature of the defined plate problem. By taking a 5% uncertain error, the corresponding Triangular Fuzzy Number (TFN) is generated. Then, by using the same, the involved governing equations are solved. The results are displayed by taking different combinations of involved fuzzy parameters , and the sensitivity of the same has been discussed in the case study. Finally, it is observed that the width of  is more the mean, and the heat input rate is more sensitive than convection heat transfer.